1) 5x²-(2x+1)(x-2)-x(3x+3)+7 2) (5x-2)(x+1)-(x-3)(5x+1)-17(x-2)

Question

1) 5x²-(2x+1)(x-2)-x(3x+3)+7
2) (5x-2)(x+1)-(x-3)(5x+1)-17(x-2)

in progress 0
Everleigh 1 ngày 2021-09-19T16:48:54+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-09-19T16:49:57+00:00

    Đáp án:

     

    Giải thích các bước giải:1)5x^2-2x^2 + 3x – 3x^2 -3x+7

    =7

    2)5x^2+3x-2 – 5x^2+14x+3-17x+34

    =32

     

    0
    2021-09-19T16:50:03+00:00

    Đáp án:

     1) S= {5/6}

    2) S={53}

    Giải thích các bước giải:

    1) 5x²-(2x+1)(x-2)-x(3x+3)+7

    ⇔ 5x²-2x²-4x+x-2-3x²-3x+7

    ⇔5x²-2x²-4x+x-2-3x²-3x+7=0

    ⇔ -6x+5=0

    ⇔ -6x=-5

    ⇔ x= $\frac{5}{6}$ 

    S={$\frac{5}{6}$ }

    2) (5x-2)(x+1)-(x-3)(5x+1)-17(x-2)

    ⇔ 5x²+5x-2x-2 – 5x²-14x-3-17×34

    ⇔ 5x²+5x-2x-2 – 5x²-14x-3-17×34=0

    ⇔11x-583=0

    ⇔ 11x= 583

    ⇔ x= 53

    S={53} 

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )